2022
DOI: 10.5897/jmsbs2021.0026
|View full text |Cite
|
Sign up to set email alerts
|

Taurine is a future biomolecule for potential health benefits: A review

Abstract: Taurine is a sulfur-containing amino acid that is converted to a neutral beta-amino acid, chemically known as (2-Amino-ethane sulfonic acid) having chemical formula C 2 H 7 NO 3 S. It was first isolated from Ox bile, and thus derives its name from the Latin word "Taurus", meaning 'ox' or 'bull'. This is the only amino acid that is extensively found in animal tissue. The richest source of taurine is meat whereas fish, human tissue, large intestine, and human breast milk are also good/prime sources. It is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Since taurine is a naturally occurring amino acid, it is expected to have minimal adverse effects on the body. Toxicity studies have indicated that it does not exhibit genotoxic, carcinogenic, or teratogenic properties ( Jakaria et al, 2019 ; Srivastava et al, 2022 ). Nevertheless, a few research studies have indicated acceptable taurine limits based on the No Observed Adverse Effect Level (NOAEL) ( Cantafora et al, 1986 ; Duan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since taurine is a naturally occurring amino acid, it is expected to have minimal adverse effects on the body. Toxicity studies have indicated that it does not exhibit genotoxic, carcinogenic, or teratogenic properties ( Jakaria et al, 2019 ; Srivastava et al, 2022 ). Nevertheless, a few research studies have indicated acceptable taurine limits based on the No Observed Adverse Effect Level (NOAEL) ( Cantafora et al, 1986 ; Duan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study shows that taurine supplementation may slow down the aging process, thus benefiting older individuals 8 .…”
Section: Anti-aging Effectsmentioning
confidence: 99%
“…Taurine has received interest in infant formula, dietary supplements and energy drinks due to its possible medicinal applications 7 . Clinical investigations demonstrate that taurine is a necessary ingredient in several species, such as cats and foxes 8 . Taurine is categorized as a conditionally necessary or useful nutrient in humans, with higher tissue retention than in cats or foxes 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation